Cognitive Restoration Design: A Psychological Intervention for Stress Mitigation in Neighbourhood Park - Syed Othman Thani, Sharifah Khalizah; Hussein, Hazreena; Cheok, Ng Siew (Online Journal for TVET Practitioners, 2023)
Numerous research studies have revealed the landscape’s positive effects on human health and well-being. While prior research underscores landscapes' positive impact on well-being, a gap still needs to be in comprehending their influence on psychological and cognitive aspects. This research focuses on how landscape attributes, specifically those seen in neighbourhood parks, may serve as a stress-relieving cognitive stimulus. In this study, we utilised qualitative research design by employing an in-depth expert interview method to explore what causes stress in urban communities and how specific landscape attributes can improve mental health and well-being. A total of 12 experts consisting of clinical psychologists, counsellors, neuropsychologists, therapists, landscape professionals and academia have consented to participate in this interview. The results illuminate a conceptual framework illustrating how psychological and cognitive landscape attributes can effectively promote cognitive restoration. The findings indicate that the design must be human centred as people are born with innate sense, intuition, and preference, all of which should be considered while designing for their psychological needs. Particularly to stimulate the cognitive part, providing landscape design elements that could inspire enthusiasm is important. This could encourage people to go to the park and interact with various stress-relieving landscape stimuli. Hence, designing for user comfort, safety, social interaction, and pleasurable experiences is critical for achieving cognitive restoration goals.